La Volatilité Du Marché Boursier Marocain: Un Comportement Hors Norme (Global Journal of Management and Business Research, 2023)
This paper aims to model the volatility of Moroccan Stock Exchange and evaluate the predictive performance of volatility models during 2005-2020. Through an empirical study, we show that the closing price of MADEX and MASI index has some empirical characteristics known as "stylized facts" which make the standard models of volatility unable to replicate their characteristics. We use the GARCH, EGARCH, APARCH, FIGARCH and FIEGARCH models to estimate the volatility of the Moroccan Stock Exchange. The first result shows that the volatility of the Moroccan stock market does not behave similarly to the volatility of the international stock markets because she reacts to negative shocks and positive shocks. A second result shows that the FIGARCH and FIEGARCH models provide superior performance than the other GARCH volatility models which is an indicator of the presence of a long memory in the volatility process.
Keywords: stylized facts; volatility; GARCH models; long memory